Systemic treatments in MDM2 positive intimal sarcoma: A multicentre experience with anthracycline, gemcitabine, and pazopanib within the World Sarcoma Network. Issue 1 (19th September 2019) - Frezza, Anna Maria; Assi, Tarek; Lo Vullo, Salvatore; Ben‐Ami, Eytan; Dufresne, Armelle; Yonemori, Kan; Noguchi, Emi; Siontis, Brittany; Ferraro, Richard; Teterycz, Pawel; Duffaud, Florence; Ravi, Vinod; et al.
Abstract : Background: Intimal sarcoma (InS) is an exceedingly rare neoplasm with an unfavorable prognosis, for which new potentially active treatments are under development. We report on the activity of anthracycline‐based regimens, gemcitabine‐based regimens, and pazopanib in patients with InS. Methods: Seventeen sarcoma reference centers in Europe, the United States, and Japan contributed data to this retrospective analysis. Patients with MDM2‐positive InS who were treated with anthracycline‐based regimens, gemcitabine‐based regimens, or pazopanib between October 2001 and January 2018 were selected. Local pathological review was performed to confirm diagnosis. Response was assessed by RECIST1.1. Recurrence‐free survival (RFS), progression‐free survival (PFS) and overall survival were computed by Kaplan‐Meier method. Results: Seventy‐two patients were included (66 anthracycline‐based regimens; 26 gemcitabine‐based regimens; 12 pazopanib). In the anthracycline‐based group, 24 (36%) patients were treated for localized disease, and 42 (64%) patients were treated for advanced disease. The real‐world overall response rate (rwORR) was 38%. For patients with localized disease, the median RFS was 14.6 months. For patients with advanced disease, the median PFS was 7.7 months. No anthracycline‐related cardiac toxicity was reported in patients with cardiac InS (n = 26). For gemcitabine and pazopanib, the rwORR was 8%, and the median PFS was 3.2 and 3.7 months, respectively. Conclusion: This retrospective series shows the activity of anthracycline‐based regimens in InS. Of note, anthracyclines were used in patients with cardiac InS with no significant cardiac toxicity. The prognosis in patients with InS remains poor, and new active drugs and treatment strategies are needed. Abstract : Anthracycline‐based regimens are a potentially effective medical option in intimal sarcoma. Of note, anthracyclines were used to treat primary cardiac tumors, with no significant cardiac toxicity reported. The value of gemcitabine and pazopanib is limited, but these agents could nonetheless be used as further‐line therapy or in patients unfit for anthracyclines.